1‐(1H‐Indol‐3‐yl)ethanamine Derivatives as Potent Staphylococcus aureus NorA Efflux Pump Inhibitors. Issue 7 (26th March 2014) - Hequet, Arnaud; Burchak, Olga N.; Jeanty, Matthieu; Guinchard, Xavier; Le Pihive, Emmanuelle; Maigre, Laure; Bouhours, Pascale; Schneider, Dominique; Maurin, Max; Paris, Jean‐Marc; Denis, Jean‐Noël; Jolivalt, Claude
Abstract The synthesis of 37 1‐(1H‐indol‐3‐yl)ethanamine derivatives, including 12 new compounds, was achieved through a series of simple and efficient chemical modifications. These indole derivatives displayed modest or no intrinsic anti‐staphylococcal activity. By contrast, several of the compounds restored, in a concentration‐dependent manner, the antibacterial activity of ciprofloxacin against Staphylococcus aureus strains that were resistant to fluoroquinolones due to overexpression of the NorA efflux pump. Structure–activity relationships studies revealed that the indolic aldonitrones halogenated at position 5 of the indole core were the most efficient inhibitors of the S. aureus NorA efflux pump. Among the compounds, (Z)‐N‐benzylidene‐2‐(tert‐butoxycarbonylamino)‐1‐(5‐iodo‐1H‐indol‐3‐yl)ethanamine oxide led to a fourfold decrease of the ciprofloxacin minimum inhibitory concentration against the SA‐1199B strain when used at a concentration of 0.5 mg L−1. To the best of our knowledge, this activity is the highest reported to date for an indolic NorA inhibitor. In addition, a new antibacterial compound, tert‐butyl (2‐(3‐hydroxyureido)‐2‐(1H‐indol‐3‐yl)ethyl)carbamate, which is not toxic for human cells, was also found.